Nanoscale structural analysis of Pb(Mg1/3Nb2/3)O3. (16th October 2020) - Yoneda, Yasuhiro; Taniguchi, Hiroki; Noguchi, Yuji
Abstract: The determination of local atomic structure at nanoscale for inhomogeneous systems is challenging. The local arrangement of atoms needs to be studied to understand the local or short-range order structures for disordered materials with a lack of long-range order periodicity. Pair distribution function (PDF) analysis is a technique, that is used to study the short-range order structure of materials: this technique is based on the evaluation of local atomic arrangement using synchrotron and neutron sources. An attempt was made to determine the local arrangement at 20 nm-scale for a typical relaxor ferroelectric material, Pb(Mg1/3 Nb2/3 )O3 (PMN). The PDF technique was employed owing to the limited structural coherence in this disordered material. It was determined that there are three types of structures depending on the distance. A glass-like network structure was observed as a short-range order structure owing to the large off-center shift of lead atoms. With an increase in distance, the structure of PMN changed from rhombohedral to cubic. Using the above-mentioned approach, we elucidated the process of local structure averaging.